1995
DOI: 10.1006/viro.1995.1219
|View full text |Cite
|
Sign up to set email alerts
|

Efficient Interaction of the Vesicular Stomatitis Virus P Protein with the L Protein or the N Protein in Cells Expressing the Recombinant Proteins

Abstract: Specific in vivo interaction between the phosphoprotein (P) and the large polymerase protein (L) from the Indiana serotype of vesicular stomatitis virus was studied using a two-hybrid system. Transfection of CHO cells with plasmids encoding GALPIND and VPLIND fusion proteins resulted in an easily detectable level of CAT activity, indicating that PIND and LIND associate in vivo in the absence of other viral proteins. Mutational studies of PIND demonstrated that both domains I and II of PIND are important for PI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

4
21
0

Year Published

1997
1997
2010
2010

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 31 publications
(25 citation statements)
references
References 0 publications
4
21
0
Order By: Relevance
“…This permitted us to reinvestigate the role of the VSV P protein as a solubility factor for the N protein and as a potential component in the assembly pathway of the VSV RNP. We found the C-terminal domain of the P protein was important for the interaction between the N and P proteins, which is in agreement with previous descriptions (17,41,42). Takacs et al demonstrated that as few as the final 10 C-terminal residues of FIG.…”
Section: Discussionsupporting
confidence: 92%
“…This permitted us to reinvestigate the role of the VSV P protein as a solubility factor for the N protein and as a potential component in the assembly pathway of the VSV RNP. We found the C-terminal domain of the P protein was important for the interaction between the N and P proteins, which is in agreement with previous descriptions (17,41,42). Takacs et al demonstrated that as few as the final 10 C-terminal residues of FIG.…”
Section: Discussionsupporting
confidence: 92%
“…The fact that the main L binding domain (residues 40 to 70) would then mostly correspond to a predicted disordered region of the P protein (mapped as residues 56 to 91) (13) could be a guarantee for flexibility, and N°bound to the NH 2 end of P could serve as a chaperone for the L binding site. Finally, the L binding site in position 40 to 70/100 on P is consistent with the observation that the domain of residues 79 to 123 of the P protein of VSV is critical for binding to L (11), possibly through phosphorylation of Ser and Thr residues between residues 49 to 64 (43). Interestingly, Ser 63 to 64 of the RABV CVS strain located in a related position (Fig.…”
Section: Discussionsupporting
confidence: 85%
“…Therefore, if N-protein conformational changes resulting from N-N interactions are required for N-P interactions, these must reside within N-terminal half of the protein. In contrast, with VSV and RV, C-terminal amino acids are required for N-P associations (30,31). Although we have not evaluated SYNV RNA binding, the P protein of VSV is required for specific binding of the N protein to viral RNA in vitro (23,24), and encapsidation of the leader RNA requires the five C-terminal residues of the N protein (6).…”
Section: Discussionmentioning
confidence: 99%